The Role of Seismic and Slow Slip Events in Triggering the 2018 M7.1 Anchorage Earthquake in the Southcentral Alaska Subduction Zone. Issue 10 (20th May 2020) - Segou, M.; Parsons, T.
Abstract: The M 7.1 2018 Anchorage earthquake occurred in the bending part of the subducting North Pacific plate near the geometrical barrier formed by the underthrusting Yakutat terrane. We calculate the triggering potential related with stress redistribution from deformation sources including the M 9.2 1964 earthquake coseismic slip, postseismic deformation, slip from regional M > 5 earthquakes, and the cumulative slip of previously detected slow slip events over the past 55 years. We investigate the deeper shallow depth (20–60 km) seismicity response to these perturbations using an epidemic type aftershock sequence model to describe earthquake‐to‐earthquake interactions. The statistical forecast captures the triggered seismicity during the 1983 M 6+ aftershocks in Columbia Bay but performs poorly during the slow slip event period between 1992.0 and 2004.8 that presents a statistically significant rate change ( β, Z > 2; M < 4.0). We find that stress effects from the 1964 postseismic source and the 12‐year‐long slow slip event ( M 7.8) contribute to the 2018 Anchorage earthquake occurrence and that slow slip events modulate the deeper shallow depth seismicity patterns in the region. Plain Language Summary: The 2018 M 7.1 Anchorage earthquake happened within a bending part of the downgoing slab beneath Southcentral Alaska. The earthquake was encouraged by stress accumulation caused by slow slip on the interface between the slab and the North American plate. Slow slip events also more than doubled the M ≥ 3 earthquake rate in the Cook Inlet beginning in the 1990s. Key Points: Stress effects from the 1964 postseismic source and a long‐lasting slow slip event promoted the recent 2018 Anchorage event The slow slip events occur in the 1964 stress shadow, farther downdip of the 1964 coseismic slip distributions but within the upper limit of its afterslip The slow slip events modulate the deeper shallow depth low magnitude seismicity and capture the post‐1964 triggered seismicity